Electrolyte Effects on the Stabilization of Prussian Blue Analogue Electrodes in Aqueous Sodium-Ion Batteries - Lamprecht, Xaver; Speck, Florian; Marzak, Philipp; Cherevko, Serhiy; Bandarenka, Aliaksandr S. (ACS Applied Materials and Interfaces, 2022)
Aqueous sodium-ion batteries based on Prussian Blue Analogues (PBA) are considered as promising and scalable candidates for stationary energy storage systems, where longevity and cycling stability are assigned utmost importance to maintain economic viability. Although degradation due to active material dissolution is a common issue of battery electrodes, it is hardly observable directly due to a lack of in operando techniques, making it challenging to optimize the performance of electrodes. By operating Na2Ni[Fe(CN)6] and Na2Co[Fe(CN)6] model electrodes in a flow-cell setup connected to an inductively coupled plasma mass spectrometer, in this work, the dynamics of constituent transition-metal dissolution during the charge-discharge cycles was monitored in real time. At neutral pHs, the extraction of nickel and cobalt was found to drive the degradation process during charge-discharge cycles. It was also found that the nature of anions present in the electrolytes has a significant impact on the degradation rate, determining the order ClO4- > NO3- > Cl- > SO42- with decreasing stability from the perchlorate to sulfate electrolytes. It is proposed that the dissolution process is initiated by detrimental specific adsorption of anions during the electrode oxidation, therefore scaling with their respective chemisorption affinity. This study involves an entire comparison of the effectiveness of common stabilization strategies for PBAs under very fast (dis)charging conditions at 300C, emphasizing the superiority of highly concentrated NaClO4 with almost no capacity loss after 10 »000 cycles for Na2Ni[Fe(CN)6].
CRIS-Team Scopus Importer:2022-04-01
Keywords: active material dissolution; degradation; ICP-MS; Na-ion aqueous batteries; Prussian Blue Analogues; sodium nickel hexacyanoferrate